1988
DOI: 10.1073/pnas.85.11.3875
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mutagen-activated cellular oncogenes that confer anchorage independence to human fibroblasts and tumorigenicity to NIH 3T3 cells: sequence analysis of an enzymatically amplified mutant HRAS allele.

Abstract: Treatment of diploid human fibroblasts with an alkylating mutagen has been shown to induce stable, anchorage-independent cell populations at frequencies (11 X 10-4) consistent with an activating mutation. After treatment of human foreskin fibroblasts with the mutagen benzo[alpyrene (±)anti-7,8-dihydrodiol 9,10-epoxide and selection in soft agar, 17 anchorage-independent clones were isolated and expanded, and their cellular DNA was used to cotransfect NIH 3T3 cells along with pSV2neo. DNA from 11 of the 17 clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Quantitatively, the most important of these metabolites is (7R,8S)-dihydroxy-(9S,10R)-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene which is the ultimate carcinogen binding DNA at the guanine residues and producing DNA adducts. The DNA binding will activate the H-ras and K-ras oncogenes [1172][1173][1174][1175] and other oncogenes such as c-Jun, E6 and E7 [1176][1177][1178][1179]. B[a]P 7,8-dihydrodiol is a bay-region diolepoxide that can be reduced to catechol which is further oxidized to generate a reactive quinine metabolite.…”
Section: Benzo[a]pyrene (B[a]p)mentioning
confidence: 99%
“…Quantitatively, the most important of these metabolites is (7R,8S)-dihydroxy-(9S,10R)-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene which is the ultimate carcinogen binding DNA at the guanine residues and producing DNA adducts. The DNA binding will activate the H-ras and K-ras oncogenes [1172][1173][1174][1175] and other oncogenes such as c-Jun, E6 and E7 [1176][1177][1178][1179]. B[a]P 7,8-dihydrodiol is a bay-region diolepoxide that can be reduced to catechol which is further oxidized to generate a reactive quinine metabolite.…”
Section: Benzo[a]pyrene (B[a]p)mentioning
confidence: 99%
“…However, one study reported that anti-BPDE forms the H-ras codon 12 GGC to GTC mutation in NIH3T3 cells to induce anchorage independence [100]. The solitary BPDE-induced papilloma obtained in our study contained the H-ras codon 13 GGC to GTC mutation (Table 1).…”
Section: Mutagenesis By Bp and Metabolitesmentioning
confidence: 91%
“…Cellular DNA was extracted as described [26]. DNA was cut with restriction endonucleases according to the manufacturer's recommendation.…”
Section: Southern Blot Analysis For Plasmid Dnamentioning
confidence: 99%